Prevalence and factors associated with dating violence among public school adolescents - Ana Virginia Rodrigues Veríssimo; Elivalda Andrade Silva; Karla Hellen Dias Soares; Eveline Lorena da Silva Amaral; Waldemar Brandão Neto; Ana Bernarda Ludermir; Estela Maria Leite Meirelles Monteiro; Jael Maria de Aquino (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective Identify the prevalence and factors associated with dating violence among school adolescents. Method Quantitative, descriptive, cross-sectional study, conducted in a state public school in Recife, Pernambuco, in August 2018, with 270 adolescents, aged between 12 and 19 years, from middle and high school. A form was applied with questions about the characterization of the adolescents, the experience of dating relationships, and the Conflict in Adolescent Dating Relationships Inventory. Pearson's chi-square test or Fisher's exact test was used for statistical analysis. Results The prevalence of physical, sexual, and psychological victimization was 31.9%, 36.4% and 81.8%, respectively. An association was identified between religious affiliation (p = 0.002), sexual orientation of the participants (p = 0.027), and parents' education (p = 0.015) and physical victimization during dating. Conclusion Individual and contextual aspects related to dating violence among adolescents imply the need for the involvement of the school nurse in intersectoral and interdisciplinary health interventions.